Balloon-Assisted Enteroscopy and Capsule Endoscopy in Suspected Small Bowel Crohn's Disease - Hsu-Heng Yen; Chen-Wang Chang; Jen-Wei Chou; Shu-Chen Wei (Korean Society of Gastrointestinal Endoscopy, 2017)
Inflammatory bowel diseases are idiopathic inflammatory diseases of two main types, Crohn's disease and ulcerative colitis. Crohn's disease can affect the entire gastrointestinal tract, and the distal ileum is involved in up to 70% of patients. Moreover, Crohn's disease in one-quarter to one-third of patients involves isolation of the small bowel. Due to the nonspecific symptoms and anatomical location of the disease, small bowel Crohn's disease is a phenotype that is particularly difficult to manage. Since the introduction of capsule endoscopy in 2000 and balloon-assisted enteroscopy in the 21st century, it is now possible to directly inspect for small bowel Crohn's disease. However, the new modalities still have limitations, such as capsule retention and invasiveness of balloon-assisted enteroscopy. The diagnostic yields of both capsule endoscopy and balloon-assisted enteroscopy are high for patients with suspected small bowel Crohn's disease. Therefore, earlier use of capsule endoscopy or balloon-assisted enteroscopy can help with the diagnosis and earlier treatment of these patients to avert possible disastrous outcomes.